Family caregiving in dementia and its impact on quality of life and economic burden in Japan-web based survey. Issue 1 (1st January 2020) - Igarashi, Ataru; Fukuda, Ayako; Teng, Lida; Ma, Fan-Fan; Dorey, Julie; Onishi, Yoshie
ABSTRACT: Background : Dementia has become a growing health-care problem in the rapidly ageing Japanese population. This study assesses the impact of dementia on quality of life, economic burden, and productivity loss. Objective : The objective of this study was to assess the impact of dementia on the Quality of Life (QoL), economic burden, and productivity loss among families living with dementia. Methods : An online survey was conducted among families who lived with relatives with dementia. Demographic data and information about health condition and costs of long-term care and treatment were collected. Participants were asked to answer the EuroQol (EQ-5D-5L) questionnaire, Zarit Burden Interview (ZARIT-8), and Work Productivity and Activity Impairment Questionnaire (WPAI). Multivariate analyses were conducted to assess factors associated with burden by families living with dementia. Results : Six hundred and thirty-five participants completed the survey. Of these participants, 50.5% were primary caregivers. Overall, 78.7% of dementia patients suffered from Alzheimer, and 43.9% needed long-term care. Compared to non-primary caregivers, primary caregivers had lower health utility scores (0.896 vs 0.873; p = 0.02), higher burden of caregiving (ZARIT-8: 21.1 vs 24.5; p < 0.0001), and higher overall work impairment (40.2% vs 20.8%; p < 0.0001), absenteeism (15.3% vs 5.7%; p < 0.0001), and presenteeism-related impairment (33.2% vs 17.3%; p < 0.0001). Conclusion : Families living with dementia caring for a person with dementia experience increased burden. Health policies related to dementia need to be considered not only for patients, but also for their families living with dementia to improve their QoL.